A Critique of a Satire - Constantine Acropolites’ Letter on the Timarion - Mészáros, Tamás (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
The protagonist of the satire Timarion, by an unknown author from the 11th or 12th century, falls into a state of suspended animation on his journey and is carried by two demons into the underworld, where he proves in a court trial that he is not dead and is allowed to return to the living. The aim of this paper is to present and interpret a short letter written two hundred years later by Constantine Acropolites, who sharply criticises the Timarion, without clearly presenting his objections.